Protocol for a systematic review and meta-analysis of pharmacological and non-pharmacological interventions for chronic pain management in chronic kidney disease - Chi Peng Chan; Babaniji Omosule; Courtney Lightfoot; Ellesha A. Smith; Ffion Curtis; James O. Burton; Paul Gardner; Sarah Jasat; Sherna F. Adenwalla; Jyoti Baharani; Daniel S. March (PLoS ONE, 2026)
Background Chronic pain affects up to 60% of people with chronic kidney disease (CKD), yet remains under-recognised and under-treated. Pain management in this population is complicated by altered drug pharmacokinetics, polypharmacy, and the potential nephrotoxicity of conventional analgesics. Despite the high prevalence and significant impact on quality of life, evidence-based guidance specific to pain management in CKD remains limited. Objectives This systematic review aims to evaluate the effectiveness and safety of both pharmacological and non-pharmacological interventions in reducing chronic pain intensity among people with CKD on dialysis, not on dialysis, and kidney transplant recipients, across all stages of CKD. Methods The primary outcome is the effectiveness of interventions in reducing chronic pain intensity as assessed by pain assessment tools. We will conduct a comprehensive search of MEDLINE, Embase, CINAHL, Web of Science, and ClinicalTrials.gov from their inception to the present date to identify studies for chronic pain management in people living with CKD. Study screening will be conducted independently by two reviewers. One reviewer will extract data from each study, with a second reviewer cross-checking for accuracy and completeness. Data will be extracted on study characteristics, participant demographics, intervention components, pain outcomes, and adverse events. The certainty of evidence will be evaluated independently by two reviewers using the GRADE approach. Where applicable, data will be combined in meta-analyses using random-effects models. Additionally, a network meta-analysis will be performed if enough studies are available. Expected results This review will synthesise the current evidence for pain management strategies in CKD, by evaluating effectiveness of interventions among people receiving different renal replacement therapy modalities with varying pain and disease phenotypes. Findings will highlight the comparative effectiveness of various interventions while considering their safety profiles specific to the CKD context. The review will identify gaps in the literature and provide recommendations for clinical practice and future research. Significance This review seeks to deliver a thorough evaluation of pain management strategies for people living with CKD. This systematic review is supported by the UK Kidney Association (UKKA), and findings will inform the upcoming UKKA guideline on symptoms management in people with CKD, alongside the other symptoms including itch, fatigue, and gastrointestinal symptoms. This review will aid clinicians in making well-informed decisions regarding pain management strategies, ensuring a balance between effectiveness and the specific risks associated with CKD.